Foreign Peer Effects and STEM Major Choice - Massimo Anelli; Kevin Y. Shih; Kevin Williams (Institute of Labor Economics (IZA), 2017)
Since the 1980s the United States has faced growing disinterest and high attrition from STEM majors. Over the same period, foreign-born enrollment in U.S. higher education has increased steadily. This paper examines whether foreign-born peers affect the likelihood American college students graduate with a STEM major. Using administrative student records from a large public university in California, we exploit idiosyncratic variation in the share of foreign peers across introductory math courses taught by the same professor over time. Results indicate that a 1 standard deviation increase in foreign peers reduces the likelihood native-born students graduate with STEM majors by 3 percentage points equivalent to 3.7 native students displaced for 9 additional foreign students in an average course. STEM displacement is offset by an increased likelihood of choosing Social Science majors. However, the earnings prospects of displaced students are minimally affected as they appear to be choosing Social Science majors with equally high earning power. We demonstrate that comparative advantage and linguistic dissonance may operate as underlying mechanisms.
Keywords: I21; I23; I28; J21; J24; 330; immigration; peer effects; higher education; college major; STEM